como resolver essa equação do segundo grau?
![(15 + x)( \frac{3000 }{x} - 10) = 3000 (15 + x)( \frac{3000 }{x} - 10) = 3000](https://tex.z-dn.net/?f=%2815+%2B+x%29%28+%5Cfrac%7B3000+%7D%7Bx%7D++-+10%29+%3D+3000)
Soluções para a tarefa
Respondido por
4
Resposta:
(15+x) *(300/x -10)=3000
multiplique tudo por x
x * (15+x) *(300/x -10)=3000 * x
(15+x) *x *(300/x -10)=3000 * x
(15+x) *(300 -10x)=3000 * x
15 * (300 -10x) + x* (300 -10x) = 3000x
4500 -150x +300x -10x² =3000x
divida tudo por 10
450 -15x +30x -x² =300x
450 +15x-x²=300x
x²-15x-450+300x = 0
x²+285x -450=0
x'=[-285 + √(285²+4*450)]/2 = [-285 + √83025]/2
x'=[-285+45√41]/2
x''=[-285 - √(285²+4*450)]/2 = [-285 - √83025]/2
x''=[-285-45√41]/2
Perguntas interessantes
História,
9 meses atrás
Matemática,
9 meses atrás
História,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
(15+x) *(3000/x -10)=3000
multiplique tudo por x
x * (15+x) *(3000/x -10)=3000 * x
(15+x) *x *(3000/x -10)=3000 * x
(15+x) *(3000 -10x)=3000 * x
15 * (3000 -10x) + x* (3000 -10x) = 3000x
45000 -150x +3000x -10x² =3000x
45000 -150x -10x² =0
divida tudo por 10
4500 -15x -x² =0
x²+15x-4500=0
x'=[-15 + √(15²+4*4500)]/2
x'=[-15+135]/2=60
x''=[-15 - √(15²+4*4500)]/2
x''=[-15+135]/2=-75